Surviving Diversity Religion and democratic citizenship - Spinner-Halev, Jeff (Baltimore The Johns Hopskins University Press, 2000)
While liberal advocates of multiculturalism frequently call for tolerance of those with diverse views, this is often not extended to members of religious groups. The author offers three principles on which accommodation of exclusive religious groups shoul
Keywords: Religion and politics -- United States. Conservatism -- Religious aspects. POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights